Human Mesenchymal Stem Cell Failure to Adapt to Glucose Shortage and Rapidly Use Intracellular Energy Reserves Through Glycolysis Explains Poor Cell Survival After Implantation. (9th January 2018) - Moya, Adrien; Paquet, Joseph; Deschepper, Mickael; Larochette, Nathanaël; Oudina, Karim; Denoeud, Cyprien; Bensidhoum, Morad; Logeart‐Avramoglou, Delphine; Petite, Hervé
Abstract: Mesenchymal stem cells (MSCs) hold considerable promise in tissue engineering (TE). However, their poor survival when exogenously administered limits their therapeutic potential. Previous studies from our group demonstrated that lack of glucose (glc) (but not of oxygen) is fatal to human MSCs because it serves as a pro‐survival and pro‐angiogenic molecule for human MSCs (hMSCs) upon transplantation. However, which energy‐providing pathways MSCs use to metabolize glc upon transplantation? Are there alternative energetic nutrients to replace glc? And most importantly, do hMSCs possess significant intracellular glc reserves for ensuring their survival upon transplantation? These remain open questions at the forefront of TE based‐therapies. In this study, we established for the first time that the in vivo environment experienced by hMSCs is best reflected by near‐anoxia (0.1% O2 ) rather than hypoxia (1%–5% O2 ) in vitro. Under these near‐anoxia conditions, hMSCs rely almost exclusively on glc through anerobic glycolysis for ATP production and are unable to use either exogenous glutamine, serine, or pyruvate as energy substrates. Most importantly, hMSCs are unable to adapt their metabolism to the lack of exogenous glc, possess a very limited internal stock of glc and virtually no ATP reserves. This lack of downregulation of energy turnover as a function of exogenous glc level results in a rapid depletion of hMSC energy reserves that explains their poor survival rate. These new insights prompt for the development of glc‐releasing scaffolds to overcome this roadblock plaguing the field of TE based‐therapies. Stem Cells 2018;36:363–376 Abstract : This study demonstrated that human mesenchymal stem cells (hMSCs) located at the core of hydrogels construct implanted in vivo face a near‐anoxic microenvironment which quickly becomes ischemic when extracellular nutrients (especially exogenous glucose [glc]) are exhausted. In this ischemic environment, failure of hMSC to adapt their glc consumption to glc shortage as well as their inability to use alternative energy substrates result in a scenario where implanted hMSCs consume their glycolytic reserves through glycolysis in less than 24 hours. Once these glycolytic reserves are exhausted, hMSCs cannot maintain their ATP content and are unable to meet their bioenergetic requirements ultimately leading to an early and massive cell‐death within 3 to 7 days post‐implantation. Red arrows indicate functions that are downregulated, Green arrows indicate functions that are upregulated. Abbreviations: TCA, tricarboxylic acid cycle; PPP, pentose phosphate pathway; HIF, hypoxia‐inducible factor; LDH, lactate dehydrogenase.